2012
DOI: 10.1021/ac202948t
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Paper-Based Assay for Rapid Blood Typing

Abstract: We developed and validated a new paper-based assay for the detection of human blood type. Our method involves spotting a 3 μL blood sample on a paper surface where grouping antibodies have already been introduced. A thin film chromatograph tank was used to chromatographically elute the blood spot with 0.9% NaCl buffer for 10 min by capillary absorption. Agglutinated red blood cells (RBCs) were fixed on the paper substrate, resulting in a high optical density of the spot, with no visual trace in the buffer wick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
118
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 105 publications
(118 citation statements)
references
References 32 publications
(89 reference statements)
0
118
0
Order By: Relevance
“…The conventional sandwich ELISA technique involves plate preparation using primary antibody. Researchers have demonstrated that antibodies can be physisorbed or ink jet printed on paper, and can be used for further applications [1][2][3]46]. In this study, the paper was used as an alternative surface to perform the sandwich ELISA test to detect viruses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conventional sandwich ELISA technique involves plate preparation using primary antibody. Researchers have demonstrated that antibodies can be physisorbed or ink jet printed on paper, and can be used for further applications [1][2][3]46]. In this study, the paper was used as an alternative surface to perform the sandwich ELISA test to detect viruses.…”
Section: Discussionmentioning
confidence: 99%
“…In the detection of health conditions through pathological diagnosis, the outsourcing of blood, urine and other biofluid samples to an analytical laboratory is a standard practice. Reliable instantaneous diagnoses without recourse to sophisticated laboratory and analytical instrumentation would be a significant innovation that promises to improve health outcomes in underprivileged and remote areas [1][2][3][4]. In addition, access to simple, dependable and low cost water and air filters that are able to capture and deactivate waterborne and airborne pathogens would be equally invaluable for preventing epidemic health threats through provision of safe water and air [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] These hybrid chips can implement complex labon-a-chip techniques, which require many independently controlled flow rates, on a single monolithic chip without external instrumentation to drive fluid flow. In contrast to previous works that have demonstrated the elution of cells on paper substrates, 17,18 our hybrid chip enables cells to be controlled using conventional microfluidic structures such as single-cell capture sites, 19 inertial focusing, 20 and chaotic mixers. 21 In this paper, we demonstrate that integrated paper microchannels can be used to quantitatively control flow in conventional microchannels.…”
Section: Introductionmentioning
confidence: 95%
“…Previous paperbased tests required greater volumes of blood because of higher substrate absorbency, necessitating venepuncture [24]. Furthermore, operation of the thread-based test did not require the washing with saline or other reagents needed in paper tests [25,26], and therefore no handling of other liquids by users was necessary.…”
Section: Introductionmentioning
confidence: 99%